ANALISIS KESALAHAN BERBAHASA INDONESIA PADA KARANGAN EKSPOSISI SISWA KELAS X MIPA (STUDI KASUS DI SMA NEGERI 4 SURAKARTA) - Oktaviani, Feny; Rohmadi, Muhammad; Purwadi, Purwadi (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe and explain the form of language errors in the field of phonology, morphology, and syntax in the exposition essay of the student of X MIPA SMA N 4 Surakarta and describe the causes of language errors and efforts that can be done by teachers and students so that the Indonesian language error in the exposition essay by the students of X MIPA SMA N 4 Surakarta can be minimized. The research uses qualitative method with case study type. Research data in the form of Indonesian language error obtained through the exposition essay by the student of X MIPA and the data source used are documents and informants. Data collection technique conducted through observation, interviews, dan test. Data validity test used is triangulation method, informant review, dan intrarater. The result of this research are description of: (1) forms of language errors in the phonological field include capitalization misuse, misuse of punctuation, particle error, rewrite error, typographic error, and typing error; (2) the form of language error in the morphological field include mistakes of preposition, mistake of word formation, and error of pleonasm; (3) the form of language error in the syntax field include the phrase structure dan sentence structure; and (4) the factors causing the Indonesian language error not only comes from the students but also because of teacher and efforts that can be done to minimize language errors.